Acupuncture for IVF and assisted reproduction : an integrated approach to treatment and management - Szmelskyj, Irina; Aquilina, Lianne; Szmelskyj, Alan O.; ScienceDirect eBooks (Oxford : Churchill Livingstone, 2014)
Incorporating orthodox medical theory and the existing evidenced-base for the use of acupuncture therapy, Acupuncture for IVF and Assisted Reproduction enables acupuncture practitioners to provide appropriate advice regarding diagnoses, orthodox tests and investigations, and tailor acupuncture treatment according to the stage of the fertility cycle, and associated underlying condition. An essential manual for all practitioners working in this area, or planning to do so.
Functional Anatomy of the Reproductive System from an Orthodox Medical PerspectiveFemale reproductive anatomy; The ovaries and follicles; The fallopian tubes; Uterus; Vagina; Abnormalities of the female reproductive anatomy; Ovarian factors; Tubal factors; Uterine factors; Male reproductive anatomy; Testes; Epididymides; Vas deferens; Seminal vesicles; Ejaculatory ducts, prostate gland, and prostatic urethra; Urethra; Penis; Abnormalities of the male reproductive anatomy; Sperm and Egg Production; Spermatogenesis and spermiogenesis; Structure of sperm; Oogenesis; Structure of the egg.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Acupuncture; Reproductive technology; Fertilization in vitro; Infertility -- Treatment; Acupuncture; Fertilization in vitro; Infertility -- Treatment; Reproductive technology; Electronic books